Coumarins ameliorate diabetogenic action of dexamethasone via Akt activation and AMPK signaling in skeletal muscle - Zejun Mo; Linghuan Li; Haiwen Yu; Yingqi Wu; Hanbing Li (Elsevier, 2019)
Glucocorticoids are widely prescribed for lots of pathological conditions, however, can produce 'Cushingoid' side effects including central obesity, glucose intolerance, insulin resistance and so forth. Our study is intended to investigate the improving effects of coumarins on diabetogenic action of dexamethasone in vivo and in vitro and elucidate potential mechanisms. ICR mice treated with dexamethasone for 21 days exhibited decreased body weight, increased blood glucose and impaired glucose tolerance, which were prevented by fraxetin (40 mg/kg/day), esculin (40 mg/kg/day) and osthole (20 mg/kg/day), respectively. Esculin, fraxetin and osthole also could promote glucose uptake in normal C2C12 myotubes, and improve insulin resistance in myotubes induced by dexamethasone. Western blotting results indicated that esculin, fraxetin and osthole could boost Akt activation, stimulate GLUT4 translocation, thus alleviate insulin resistance. Esculin and osthole also could activate AMPK, thereby phosphorylate TBC1D1 at Ser237, and consequently ameliorate diabetogenic action of dexamethasone. Our study indicates coumarins as potential anti-diabetic candidates or leading compounds for drug development. Keywords: Coumarin, Osthole, Esculin, Fraxetin, Insulin resistance, Dexamethasone